2017
DOI: 10.26719/2017.23.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Level of khat dependence, use patterns, and psychological correlates in Yemen: a cross-sectional investigation

Abstract: Chronic khat use is associated with negative health consequences. However, no study has fully characterized individuals who are khat dependent. This paper examines socio-demographic and psychosocial correlates of adult khat dependence. A total of 270 khat users (129 women) in Yemen completed face-to-face interviews and provided demographic information and data on patterns of khat use, subjective mood, and sleep quality. The Severity of Dependence Scale-Khat (SDS-khat) was used to assess level of khat dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Participants who completed this study were part of a research program that had a different focus. Earlier results from that study among khat users are published elsewhere . A cross‐sectional study with a convenience sampling method was conducted in two Yemeni cities, Taiz and Sana'a.…”
Section: Methodssupporting
confidence: 68%
“…Participants who completed this study were part of a research program that had a different focus. Earlier results from that study among khat users are published elsewhere . A cross‐sectional study with a convenience sampling method was conducted in two Yemeni cities, Taiz and Sana'a.…”
Section: Methodssupporting
confidence: 68%
“…Another study reported the association between the development of oral cancer and chronic khat use (Soufi, Kameswaran, & Malatani, 1991). Previous studies described the addictive properties of khat and the presence of a range of dependence-related symptoms among Yemenis and UK and Australian populations of African provenance (Kassim, Croucher, & Al'Absi, 2013;Nakajima, Hoffman, & Al'Absi, 2017;Young, Butt, Hersi, Tohow, & Mohamed, 2016). In addition, a 2017 study carried out in Ethiopia indicated the psychological severity of khat addiction in polysubstance users (Manzar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Addiction-related symptoms consistent with the criteria listed in Diagnostic and Statistical Manual-5 (DSM-5) and International Classification of Diseases-10 (ICD-10) like persistent use and withdrawal symptoms including depression, increase in appetite and interrupted sleep are usually seen in khat users [ 2 , 10 , 24 , 30 ]. Khat use and the associated addictive behavior have been documented in Yemeni, UK residents and Australians of African origin [ 10 , 25 , 32 ]. Khat use disorder is associated with negative mood, sleep disturbances [ 25 ], age interaction in females [ 24 ], high morbidity and societal and economic costs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%